Early Post-operative CT-Angiography Imaging After EC-IC Bypass Surgery in Moyamoya Patients - Hurth, Helene; Hauser, Till-Karsten; Haas, Patrick; Wang, Sophie; Mengel, Annerose; Tatagiba, Marcos; Ernemann, Ulrike; Khan, Nadia; Roder, Constantin (Frontiers in Neurology, 2021)
Objective: To evaluate the clinical value of early postoperative computed tomographic angiography (CTA) after direct extracranial-intracranial (EC-IC) bypass surgery in moyamoya patients. Methods: A retrospective analysis of all adult moyamoya patients treated at our center from 2013 to 2019 with a direct EC-IC bypass was performed. Early postoperative CTA (within 24 hours after surgery) was compared with conventional digital subtraction angiography (DSA) 6-12 months after surgery. If available, magnetic resonance time-of-flight angiography (MR-TOF) was evaluated 3 months and 6-12 months postoperatively as well. Imaging results were analyzed and compared with CTA, MR-TOF and DSA, whereat DSA was used as the final and definite modality to decide on bypass patency. Results: A total of 103 direct EC-IC bypasses in 63 moyamoya patients were analyzed. All inclusion criteria were met in 32 patients (53 direct bypasses). In 84.9% the bypass appeared definitively, in 5.7% uncertainly and in 9.4% not patent according to early postoperative CTA. MR-TOF suggested definitive bypass patency in 86.8% 3 months after surgery and in 93.5% 6-12 months after surgery. DSA 6-12 months postoperatively showed a patency in 98.1% of all bypasses. The positive predictive value (to correctly detect an occluded bypass) on postoperative CTA was 12.5%, the negative predictive value (to correctly detect a patent bypass) was 100% with a sensitivity of 100% and a specificity of 86.5%. Conclusion: Early postoperative CTA has a high predictive value to confirm the patency of a bypass. On the other hand, a high false positive rate of (according to CTA) occluded bypasses after direct EC-IC bypass surgery can be seen. This must be considered critically when initiating possible therapeutic measures.